2022
DOI: 10.3389/fpubh.2022.1035560
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency in dengue fever patients' coinfected with H. pylori in Pakistan. A case-control study

Abstract: IntroductionDengue fever is a vector-borne disease with an estimate of 390 million persons getting the infection each year with a significant public health impact. It has been reported DENV patients with vitamin D deficiency led to severe form of dengue infection; while H. pylori coinfection alters vitamin D receptors leading to vitamin D deficiency. We hypothesize that DENV patient's having low vitamin D along with H. pylori coinfection could have worsen dengue severity as well as vitamin D deficiency. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…H. pylori co-infection in the setting of other infectious diseases or chronic conditions seems to be additionally associated with vitamin D deficiency. One study conducted on 800 dengue fever patients, divided into two equal groups based on H. pylori co-infection status, revealed that those individuals who were positive for the infection presented significantly lower vitamin D serum levels than dengue fever controls [ 36 ]. In patients with end-stage renal failure undergoing hemodialysis, a linear positive relationship between vitamin D levels and H. pylori immunoglobulin G (IgG) serum antibodies was discovered [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…H. pylori co-infection in the setting of other infectious diseases or chronic conditions seems to be additionally associated with vitamin D deficiency. One study conducted on 800 dengue fever patients, divided into two equal groups based on H. pylori co-infection status, revealed that those individuals who were positive for the infection presented significantly lower vitamin D serum levels than dengue fever controls [ 36 ]. In patients with end-stage renal failure undergoing hemodialysis, a linear positive relationship between vitamin D levels and H. pylori immunoglobulin G (IgG) serum antibodies was discovered [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…11 A study suggests that maintaining adequate vitamin D levels through diet or supplementation may provide adequate immune protection against severe dengue illness. 12,13 A study determined that 40% of subjects had a B12 level below 200 pg/L, potentially leading to severe thrombocytopenia, slower platelet count recovery, and prolonged hospitalization in dengue fever patients. 14 A study in India analyzed the serum proteome of dengue patients, revealing significant changes in several proteins with biological functions.…”
Section: Introductionmentioning
confidence: 99%